CONFIGURATION OF VALUES AS EXPRESSION OF THE PARADIGM OF SPIRITUALITY: THEORETICAL AND EMPIRICAL ASPECTS - Aramavičiūtė, Vanda; Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 2014)
The paradigm of spirituality is becoming more and more topical factor in creating the present and the future. The paradigm of spirituality gets to the very core, to the spiritual dimension, which is frequently regarded as a level of opinion in the 21st century. Scientists from various fields relate the spiritual dimension with the spiritual human power, due to which s/he becomes an individual able to transcend the reality, to perceive oneself in the presence of transcendentalities that manifest themselves through consciousness, to disassociate from the psychophysical organism and to manage oneself. Therefore, the spiritual dimension empowers an individual with freedom and with the possibility of identifying oneself with the eternity through the phenomenon of consciousness and with engagement in meaning. This does not trivialize the importance of the psychic and physical human dimensions as it contributes to understanding the importance of the harmony and subordination of all dimensions and their dependence on the authentic individual’s determination/ underdetermination. To avoid turning the value of freedom into a deformation of the spiritual dimension, it has to surrender to truth, which since the ancient times has been linked with the values of being (the truth, the goodness and the beauty), the so-called transcendentalities that are linked with in an immanent way with each other and express relations between the concrete and the common. Spirituality may be understood as authentic relations of an individual with the world, which, together with the true, good and beautiful, penetrate into a being and extend towards the Creator. The paradigm of spirituality allows to identify the synergy of freedom and truth as the fundamental parameters of human existence. At present, the adolescents rank dignity, sensitivity and honesty highest, and the same values as ten years ago are assigned the highest priority. However, on the cognitive level, more positive evaluations of authenticity and tolerance may be observed, whereas acknowledgment of altruism, sensitivity, faith, intelligence, responsibility tends to decrease. The most considerable rise was identified in the stability of communicative experiences, whereas that of romantic ones decreased by half. It is obvious that self-concentration has a tendency to increase. In 2009, the respondents exceeded the evaluations of a spiritual individual in the evaluations of faith, sense of spiritual unity, sensitivity to the beautiful, search for purport. This is a new observation which requires a more comprehensive research as a well as highly evaluated one’s own faith and sensitivity. The paradigm of spirituality is only partially consolidated: the contour of priority values is disclosed; they further expand the dimension of freedom. However, their weight in the spread of spirituality may be not the same when the sensation of the values that reflect the truth is getting weaker.